2006
DOI: 10.1016/j.molcel.2006.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Processivity and Single-Strand Specificity of RNase II

Abstract: RNase II is a member of the widely distributed RNR family of exoribonucleases, which are highly processive 3'-->5' hydrolytic enzymes that play an important role in mRNA decay. Here, we report the crystal structure of E. coli RNase II, which reveals an architecture reminiscent of the RNA exosome. Three RNA-binding domains come together to form a clamp-like assembly, which can only accommodate single-stranded RNA. This leads into a narrow, basic channel that ends at the putative catalytic center that is complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
100
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(110 citation statements)
references
References 33 publications
9
100
1
Order By: Relevance
“…coli RNase II is the model of the RNase II family of enzymes, whose homologues are present in all three domains of life (1,11,12,44,45). The resolution of the structure of E. coli RNase II in the RNA-free and bound complex constituted a significant breakthrough (22,24). The structural study together with biochemical analysis helped to explain certain aspects of the enzyme activity and led to the proposal of a model for RNA degradation by RNase II that can be extrapolated to other family members (13,15,22,26,41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…coli RNase II is the model of the RNase II family of enzymes, whose homologues are present in all three domains of life (1,11,12,44,45). The resolution of the structure of E. coli RNase II in the RNA-free and bound complex constituted a significant breakthrough (22,24). The structural study together with biochemical analysis helped to explain certain aspects of the enzyme activity and led to the proposal of a model for RNA degradation by RNase II that can be extrapolated to other family members (13,15,22,26,41).…”
Section: Discussionmentioning
confidence: 99%
“…The determination of E. coli RNase II structure (22)(23)(24) showed that, contrary to the sequence predictions, RNase II consisted of four domains; they are two N-terminal cold shock domains (CSD1 and CSD2) involved in RNA binding, one central RNB catalytic domain, and a third RNA binding domain at the C terminus, the S1 domain (Fig. 1A).…”
mentioning
confidence: 98%
“…The catalytic activity is provided by a 10th essential subunit, Rrp44p (2,5,6). This protein is similar to RNase II in that it contains three putative RNA binding domains that flank an RNB domain (3,(7)(8)(9)(10). The RNB domain is responsible for the 3′ exonuclease activity of the exosome (3).…”
Section: Dis3 | Saccharomyces Cerevisiaementioning
confidence: 99%
“…A clamp-like assembly in the RNA-binding domain of RNase II possibly allows single-stranded RNA 3Ј-ends to enter the catalytic center and blocks doublestranded RNA. During RNA digestion in vitro, RNase II progressively slows down at double-stranded structures, resulting in products that usually contain an average 7-9-nt singlestranded overhang at the 3Ј-end (22). In contrast to RNase II, E. coli RNase R is able to degrade double-stranded RNA effectively starting from a single-stranded 3Ј-overhang.…”
Section: Discussionmentioning
confidence: 99%